The hydroid and early medusa stage of Olindias formosus (Cnidaria, Hydrozoa, Limnomedusae). (November 2014) - Patry, Wyatt; Knowles, Thomas; Christianson, Lynne; Howard, Michael
<x content-type="archive" xml:space="preserve">Abstract</x> Olindias spp. medusae are found worldwide in sublittoral tropical and sub-tropical coastal regions; their occurrence near shore can result in human envenomation events. While behaviour of medusae and human contact with medusae has been documented for the genus, the hydroid (polyp) phase of the Olindias life cycle has eluded investigators for over a century. Given the recent debate among public media and scientific communities that jellyfish blooms are increasing worldwide, there is a growing urgency to understand how and why jellyfish populations bloom. In order to understand jellyfish population dynamics, the asexual benthic phase must be studied to determine when, where, and how juvenile medusae are produced. In this study, husbandry management strategies, including the creation of artificial habitat for Olindias formosus medusae in aquaria were developed to encourage spawning and larval settlement. The resultant hydroid colony of Olindias formosus was discovered in November of 2012, utilizing the natural fluorescence of the medusa as a detection method. A description of the hydroid and early medusa stage is presented. These techniques provide a basis for locating in situ the benthic hydroid phases within this genus and other fluorescent medusae, the discovery of which may lead to a better understanding of the causative factors for jellyfish blooms.